Pengaruh Computer Anxiety dan Computer Attitude Terhadap Keahlian Menggunakan Accurate Accounting Software - Maqfira, Rizki; Sukartini, Sukartini; Endrawati, Endrawati (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
This research was conducted to determine the effect of computer anxiety and computer attitude expertise in using accurate accounting software. This research was conducted on students of the Politeknik Negeri Padang Accounting Department who have taken the course Computer Accounting II (Accurate). The research method used is method quantitative by collecting data using a questionnaire and measured using a likert scale. The method of determining the sample using a purposive sampling method with a total a sample of 169 respondents. The results of this study indicate that the computer anxiety has no effect on skills using accurate accounting software and computer attitude has no effect on skills using accurate accounting software.